Effect of NF‐κB on Myosin Heavy Chain Content and Muscle Atrophy After Laryngeal Muscle Denervation - Yang, Jing‐Jing; Hu, Rong; Wang, Hai‐Zhou; Li, Xue‐Yan; Xu, Wen (World journal of otorhinolaryngology - head and neck surgery, 2025)
Significant findings of the study: We found that inhibiting NF‐κB could delay MyHC degradation and muscle atrophy in denervated laryngeal muscles, but the effect cannot be sustained. This finding suggests the possible mechanism of NF‐κB involved in the denervated atrophy of internal laryngeal muscles. What this study adds: The study explains the dynamic changes of the internal laryngeal muscle atrophy within 14 days of denervation and the possible mechanism of NF‐κB involved in this process.